INTEGRATING RELIGIOUS VALUES INTO CHARACTER EDUCATION: EVIDENCE FROM AN ISLAMIC MADRASAH IN INDONESIA - Chadijah; Amrah Kasim; Andi Achruh; Syamsuddin (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the implementation of character education at MTsN 3 Halmahera Utara through four focal values: religiosity, honesty, tolerance, and discipline. Using a qualitative naturalistic approach, data were collected from the head of the madrasah, teachers, and students through in depth interviews, participant observation, and documentation. The findings indicate that character education is organized as a whole school culture rather than a standalone program. Religiosity is strengthened through routinized worship practices that scaffold ethical conduct and self regulation. Honesty is fostered through teacher exemplarity, trust based learning situations, and clear behavioral norms related to academic integrity and everyday responsibility. Tolerance is cultivated as a relational practice through inclusive interaction norms and respect for differences in the school community. Discipline is reinforced through consistent routines, rule clarity, and guided accountability, though its internalization remains sensitive to family support and external influences. Overall, the study shows that coherent habituation, modeling, and institutional consistency are decisive for embedding character values in students’ daily behavior and for sustaining a constructive moral climate in the madrasah. The results suggest implications for school leadership, teacher development, and family engagement. Limitations include the single site design and scope, indicating the need for comparative and longitudinal studies.